BREAKING BARRIERS OR BUILDING BRIDGES? A SYSTEMATIC REVIEW OF WOMEN ENTREPRENEURSHIP IN SMES WITHIN EMERGING ECONOMIES - Sam-Sorungbe, Olusola; Mahmood, Ishtiaque; Olori, Evwiekpamare; Begum , Mahmuda (International Journal of Small and Medium Enterprises, 2025)
Women entrepreneurs in small and medium-sized enterprises (SMEs) in emerging economies play a critical role in employment generation, community development, and inclusive growth. However, their entrepreneurial journeys are shaped by structural finance gaps, gendered cultural norms, and institutional constraints that limit opportunities for enterprise development. This study examines the dual reality of "barriers" and "bridges" influencing women-led SMEs in emerging economies. The purpose of this research is to synthesise existing empirical evidence to understand how women both encounter and respond to these constraints. The study employs a systematic review of 17 peer-reviewed journal articles published between 2000 and 2024. Articles were identified through searches conducted in Scopus, Web of Science, and ResearchRabbit, following PRISMA 2020 screening and eligibility procedures that reduced an initial dataset of 154 records to 17 that met inclusion criteria. The results show that barriers cluster around four dominant themes: restricted access to finance, gender norms shaping entrepreneurial identity and choices, institutional voids in regulatory and market systems, and exclusion from formal entrepreneurial networks. Conversely, enablers or "bridges" include microfinance and informal credit channels, digital platforms supporting market access, women-led cooperatives and associations, and psychological resilience and agency among women entrepreneurs. The major findings of the review indicate that women entrepreneurs are not only constrained by structural factors but also act as institutional actors, developing adaptive strategies that reshape entrepreneurial ecosystems in their contexts. JEL Classification Codes: L26, M13, O14, O17, J16.